Association of neutrophil to lymphocyte ratio with all-cause and cardiovascular mortality among individuals with kidney stone disease: result from NHANES, 2007-2018 - Chu, Qihui; Wu, Bin; Zhang, Zhaofu (Frontiers in Endocrinology, 2025)
BackgroundThe objective of this study is to investigate the relationship between the neutrophil-to-lymphocyte ratio (NLR) and all-cause as well as cause-specific mortality among patients with kidney stones, and to evaluate the capability of NLR as a predictor of mortality.MethodsThis study included 2,995 patients with kidney stones from the NHANES database during the period from 2007 to 2018, and subsequently linked this data with the National Death Index. The relationship between NLR and mortality was analyzed using the Cox proportional hazards model and Kaplan-Meier survival curves. Additionally, restricted cubic spline (RCS) curves were employed to explore the dose-response relationship between NLR and mortality, while time-dependent ROC curves were utilized to assess the predictive capability of NLR for mortality. Finally, the mediating effect of estimated glomerular filtration rate (eGFR) on the relationship between NLR and mortality was also analyzed.ResultsThis study ultimately included 2,995 patients with kidney stones, with a median follow-up period of 74 months. A total of 395 deaths were recorded, of which 87 were attributed to cardiovascular diseases. An NLR cut-off of 3.62 was identified as significantly associated with survival outcomes using the ‘maxstat’ package and the principle of maximum rank statistics. The restricted cubic spline plot indicates a non-linear relationship between NLR and both all-cause mortality and cardiovascular mortality. After adjusting for relevant covariates, the Cox regression analysis demonstrated that, in comparison to the lower NLR group, the higher NLR group exhibited a 1.05-fold (HR 2.05, 95% CI 1.51-2.78, P < 0.001) increased risk of all-cause mortality and a 1.99-fold (HR 2.99, 95% CI 1.89-4.72, P < 0.001) increased risk of cardiovascular mortality. Furthermore, eGFR exhibited a significant mediating effect on the relationship between NLR and mortality.ConclusionThis study found that patients with kidney stones exhibiting a high NLR have a significantly increased risk of mortality in the U.S. population. Therefore, monitoring NLR may be important for the prognosis of patients with kidney stones.